Effect of Adding Mixture of (Concrete Waste and Asphalt Waste) on the Properties of Gypseous Soil - Adnan Jayed Zedan; Rizgar Ali Hummadi; Sarah Abdullah Hussein (Tikrit Journal of Engineering Sciences, 2019)
The Gypseous soil which is used is taken from Tikrit city in Salah Aldeen governorate and specially from Tikrit University from a depth (1.5-2) m. It's type is sandy gravely with a small percentage of silt and clay while the percentage of gypsum is (34-36) %. The tests on soil are standard proctor compaction, direct shear, collapsibility and California bearing ratio. The number of samples is (70). The effect of adding concrete waste (2, 4, 6 and 8%) and waste of Asphalt mixture (2, 4, 6 and 8) % on dry soil, as well as the effect of mixture of the optimum percentages of both additions on the properties of gypseous soil, is the aim of the study. Adding concrete waste at optimum percentage (6) % causes an increase in maximum dry density at (16)% and a decrease in optimum moisture content at (5) %. Whereas adding concrete mixture waste in its optimum percentage (2) % caused a decrease in maximum dry density values with an increase of optimum moisture content, and when adding a mixture of optimum percentage of waste, an increase happened in the M.D.D.(14)% with a decrease in O.M.C. at (4) %. Adding the optimum percentage (8) % for both, the value of cohesion increases (100) % when adding concrete waste with an increase in the angle of internal friction (14)% and a decrease in collapsibility in a percentage of (90)% , while adding waste of asphalt mixture shows an increase in cohesion value (112) % with a decrease in the angle of internal friction (2) % and a decrease in collapsibility in a percentage of (90) %, when adding mixture of optimum percentages the value of cohesion increase (108) % with an increase in angle of internal friction (14)% and a decrease in collapsibility in a percentage of (91) %. Values of California Bearing Ratio in dry and soaked condition increases (49) % when adding (8) % of concrete wastes which is the optimum percentage, while adding waste of asphalt mixture causes a decrease in the value of C.B.R. and the optimum percentage is (2) % , but adding optimum percentages mixture of them causes an increase in values of (52) % in dry condition and (53)% in soaked condition.